Hukum Mandre Ade’ dalam Suku Bugis Perspektif Hukum Islam (Desa Kalobba Kab. Sinjai): Mandre Ade' Law in the Bugis Tribe from Islamic Legal Perspective (Kalobba Village, Sinjai Regency) - Awal Rifai; Iskandar, Iskandar; Azizul Wahab (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to examine the legal position of mandre ade’ within the customary legal system of the Bugis ethnic group and to analyze the perspective of Islamic law regarding its practice in society. The research employs a qualitative descriptive method in the form of field research with a normative-shar‘i approach. Data were collected through observation, interviews, and documentation. The findings reveal that, first, mandre ade’ holds a significant position within the structure of Bugis customary law, particularly in customary events such as marriage, aqiqah, and other social activities. This tradition is regarded as an expression of respect for customary values that have been passed down through generations. Second, from the perspective of Islamic law, the practice of mandre ade’ can be accepted within the framework of the Sharī‘ah under certain considerations. First, it aligns with the principle of maintaining respect for the relationship between authority and society as taught in the Qur’an and Hadith. Second, mandre ade’ may be classified as a legitimate form of ‘urf (local custom) under Islamic law, as long as it does not involve elements that contradict Sharī‘ah principles, such as acts of shirk or other prohibited practices. The implications of this study are expected to contribute to strengthening integrative studies between customary law and Islamic law, as well as to serve as a reference for communities and customary institutions in preserving local traditions that do not conflict with Islamic principles.